Perception of professors regarding the transition to emergency remote teaching in a large public university in Mexico during the pandemic (Educação e Pesquisa, 2022)
This paper presents the most relevant results from a follow-up questionnaire applied to a sample of professors from the largest public university in Mexico — the National Autonomous University of Mexico (UNAM). It further investigates the issues identified by a questionnaire applied at the start of the pandemic (whose results were also published), sending a follow-up questionnaire to the university faculty months later. The research sought to identify and describe the opinions, experiences, characteristics, and conditions in which these professors had to switch to remote teaching using technological tools during the pandemic. Data were collected by an exploratory online survey with Likert-type multiple choice and open questions applied to a non-random sample of 513 professors at UNAM. Results show that 43% of the participants considered the quality of remote teaching to be equal to classroom teaching, 23% reported an improvement, and 34% stated that it was worse. Most respondents said they spent an average of 1 to 10 hours per week on teaching activities, with assessing and providing feedback on student assignments being the most time-consuming. Clearly, the experiences and teaching activities of university professors are changing as the pandemic continues. Post-pandemic times will require a more compelling answer from higher education institutions regarding the social inequalities generated by the pandemic.